Effects of different dosages of water-based neomycin sulfate on growth performance of weanling pigs - R O Gottlob; C W Hastad; C N Groesbeck; C R Neill; N Z Frantz; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 360 weanling pigs (initially 14.1 lb and 21 ± 3 d of age, PIC) were used to determine the effects of different rates of waterbased medication on nursery pig growth performance. Pigs were given one of eight experimental treatments: negative control (no antibiotics in the feed or water); positive control with Neo-TerramycinÂ® in the feed (140 g/ton Neomycin sulfate, 140 g/ton Oxytetracycline HCl); 38.0, 75.5, or 113.5 mg of Neomycin sulfate per L of water; 100 or 200 g/ton of Neomycin sulfate in the feed; and Neo-TerramycinÂ® in the feed and 75.5 mg of Neomycin per L of water. Overall (d 0 to 24 after weaning), pigs provided Neomycin sulfate in the water, pigs fed diets containing Neomycin sulfate, and pigs fed the positive control diet had greater ADG (P<0.02) and ADFI (P<0.05) than did pigs provided nonmedicated water and feed. Pigs provided Neomycin sulfate in the water or feed also had improved F/G (P<0.05), compared with the F/G of pigs provided non-medicated feed and water. Pigs provided the combination of the positive control diet and Neomycin sulfate in the water had greater ADFI (P<0.04) and tended to have greater ADG (P<0.09) than did pigs fed the positive control with nonmedicated water or pigs fed the negative control with Neomycin sulfate in the water. Increasing Neomycin sulfate in the water improved ADG (P<0.03) and ADFI (P<0.05). Increasing Neomycin sulfate in the feed improved ADG and ADFI (P<0.01) and improved F/G (P<0.03). There were no differences in growth performance between pigs provided Neomycin sulfate in the water and in the feed. Finally, there were no water medication × feed medication interactions for the overall treatment period, but main effects for water and feed medication were significant (P<0.02) for ADG and ADFI.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Nursery pig; Antibiotics; Water; Growth; Swine